PROJETO T.I.P.O. ASSIM! - PROMOÇÃO DE SAÚDE E PROTAGONISMO COM ADOLESCENTES (Revista Contexto & Educação, 2022)
The study addresses the Project Tipo Assim! (Territoriality, intersectoriality, health promotion, protagonism and  footprint) – developed in the outskirts of a city in the State of Rio Grande do Sul (RS), Brazil. The starting point  was the question about access possibilities to teenagers in state of vulnerability and use of alcohol and other drugs  associated to psychological distress, which don’t accede to conventional mental health outpatient approach. The  aim was to encourage health and protagonism as an alternative to alcohol and other drugs consumption; enable  teenagers’ subjectivity; create access strategies, mental health care and prevention for teenagers. The theoretical  framework was psychoanalysis, the concept of sublimation was related to changing drive into cultural production.  Territoriality is brought up, associated with the national Healthcare System (SUS – Sistema Único de Saúde)  principles. The methodology of research-intervention was carried out. The project started with the studies of the  demands of the territories; the line-up of six groups for weekly meetings, with activities related to music, poetry, cooking, sensorial perception. A questionnaire with forty teenagers was carried out to support the results analysis.  As examples of answers, these were found: 97,5% of teenagers recognize themselves as protagonists, 55% joined  the project by friends invites, showing the importance of multiplication; 57,5% noticed changes in their bonds of  friendship, 37,5 % in school and 25% in the family. Construction of collective space with teenagers and the use of  cultural activities favor protagonism, subjectivity and promote health and prevent the use of alcohol and other  drugs.
Keywords: teenagers, alcohol and other drugs, subjectivity, health promotion